A novel system for teaching the in-plane vascular access technique: A simulation study. Issue 37 (17th September 2021) - Kikuchi, Mami; Asao, Takayuki; Tokumine, Joho; Lefor, Alan Kawarai; Matsushima, Hisao; Andoh, Hideaki; Tanaka, Kazumi; Kanamoto, Masafumi; Ideno, Yuki
Abstract : Abstract: The long-axis in-plane approach is amenable to ultrasound-guided central venous catheterization. However, the long-axis in-plane approach is considered difficult to learn because the needle should remain visible in the ultrasound beam during the procedure. We developed a novel competency-based modular system to acquire the skills for the long-axis in-plane approach. The purpose of this study is to evaluate the efficacy of this system. The study was approved by the local ethics committee. Participants performed ultrasound guided venous catheterization (pre-test), attended a 2-hour hands-on session with the teaching system and were then evaluated again (posttest). The teaching system is a simulator device consisting of an ultrasound probe, a simulated vessel, a needle, and an endoscope connected to a computer to visualize the image inside the simulated vessel. The success rate, visualization of the needle tip, and puncture accuracy were measured before and after training. The puncture accuracy was determined by evaluating the distance of the needle tip and needle shaft from the center of a simulated vessel. Primary outcomes were the success rate and the puncture accuracy. The secondary outcome was needle tip visualization. McNemar test was used to analyze success rate and needle tip visualization. Tukey test was used to analyze puncture accuracy. A P value <.05 was considered statistically significant. Forty-seven participants were enrolled in this study. The success rate was significantly increased (pre-test 79%, posttest 94%, P = .04). Ultrasound images from 42 participants were analyzed for puncture accuracy. Puncture accuracy significantly increased for needle tip distance ( P = .03), but not shaft distance ( P = .1). The needle tip visualization was significantly improved ( P = .02). A novel competency-based teaching system was constructed in a step-by-step manner, which improved needle tip visualization and puncture accuracy, with a higher success rate.